DOES EMPLOYEE RETENTION IMPACT TURNOVER INTENTION? AN EXPLORATION OF THE MEDIATING ROLE OF JOB SATISFACTION - Kusuma, Bayu; Rumijati, Aniek; Febriani, Rizki; Hakim, Arif Rahman (Universitas Pakuan, 2024)
ABSTRACT This study aims to examine the effect of employee retention on turnover intention, both directly and through the mediation of job satisfaction. The population in this study were employees of CV Sido Raya Utama Sidoarjo, with a total of 42 employees using total sampling technique. The method used is path analysis with data collection using questionnaires. The results of this study indicate that employee retention reduces turnover intention while increasing job satisfaction. In addition, job satisfaction has a negative impact on turnover intention and acts as a mediator between employee retention and turnover intention. These findings indicate the importance of an effective employee retention strategy to increase job satisfaction and reduce turnover intention. Companies must create retention policies that can improve employee welfare and satisfaction to reduce high turnover rates. ABSTRAK Penelitian ini bermaksud untuk menguji pengaruh retensi karyawan terhadap turnover intention, baik secara langsung maupun melalui mediasi kepuasan kerja. Populasi dalam penelitian ini adalah karyawan CV Sido Raya Utama Sidoarjo, dengan jumlah 42 karyawan dengan menggunakan teknik total sampling. Metode yang digunakan adalah analisis jalur dengan pengumpulan data menggunakan kuesioner. Hasil penelitian ini menunjukkan bahwa retensi karyawan mengurangi turnover intention sekaligus meningkatkan kepuasan kerja. Selain itu, kepuasan kerja berdampak negatif terhadap turnover intention dan bertindak sebagai mediator antara retensi karyawan dan turnover intention. Temuan ini menunjukkan pentingnya strategi retensi karyawan yang efektif untuk meningkatkan kepuasan kerja dan mengurangi turnover intention. Perusahaan harus membuat kebijakan retensi yang dapat meningkatkan kesejahteraan dan kepuasan karyawan untuk mengurangi tingkat turnover yang tinggi.